Fatty acid‐binding protein 3 controls contact hypersensitivity through regulating skin dermal Vγ4+ γ/δ T cell in a murine model. Issue 6 (4th November 2020) - Kobayashi, Shuhei; Phung, Hai The; Kagawa, Yoshiteru; Miyazaki, Hirofumi; Takahashi, Yu; Asao, Atsuko; Maruyama, Takashi; Yoshimura, Akihiko; Ishii, Naoto; Owada, Yuji
Abstract: Background: Fatty acid‐binding protein 3 (FABP3) is a cytosolic carrier protein of polyunsaturated fatty acids (PUFAs) and regulates cellular metabolism. However, the physiological functions of FABP3 in immune cells and how FABP3 regulates inflammatory responses remain unclear. Methods: Contact hypersensitivity (CHS) induced by 2, 4‐dinitrofluorobenzene (DNFB) and fluorescein isothiocyanate was applied to the skin wild‐type and Fabp3 −/− mice. Skin inflammation was assessed using FACS, histological, and qPCR analyses. The development of γ/δ T cells was evaluated by a co‐culture system with OP9/Dll1 cells in the presence or absence of transgene of FABP3. Results: Fabp3‐deficient mice exhibit a more severe phenotype of contact hypersensitivity (CHS) accompanied by infiltration of IL‐17‐producing Vγ4 + γ/δ T cells that critically control skin inflammation. In Fabp3 −/− mice, we found a larger proportion of Vγ4 + γ/δ T cells in the skin, even though the percentage of total γ/δ T cells did not change at steady state. Similarly, juvenile Fabp3 −/− mice also contained a higher amount of Vγ4 + γ/δ T cells not only in the skin but in the thymus when compared with wild‐type mice. Furthermore, thymic double‐negative (DN) cells expressed FABP3, and FABP3 negatively regulates the development of Vγ4 + γ/δ T cells in the thymus. Conclusions: These findings suggest that FABP3 functions as a negative regulator of skin inflammation through limiting pathogenic Vγ4 + γ/δ T‐cell generation in the thymus. Abstract : FABP3 negatively regulates the differentiation of thymic DN2 cells into Vγ4 + γ/δ T cells. FABP3‐deficient mice exhibit higher frequency of Vγ4 + γ/δ T cells in skin of both juvenile and adults. FABP3 deficiency in Vγ4 + γ/δ T cells enhances production of high amounts of IL‐17A, which contributes to the pathogenesis of contact hypersensitivity. DN2, double negative cell; FABP3, fatty acid‐binding protein 3; KO, knockout. Abbreviations: DN2, double negative cell; FABP3, fatty acid‐binding protein 3; KO, knockout.